Penerapan Metode Simpleks Untuk Memaksimumkan Keuntungan pada PD. Meubeul Dua Saudara - Fajri, Moch Dzulfan; Cahyadi, Ujang (Jurnal Kalibrasi, 2024)
This research was conducted in PD. Furniture Two Brothers. which is located on Jl.Terusan Pembangunan, Kec.Tarogong Kidul, Garut Regency, West Java Province. This company produces furniture made of wood, such as door frames, window frames, doors and shutters, in some of these products the company provides different types of wood, namely mahogany and teak wood, with an amount of 1,5 m3 for mahogany wood and 2.5 m3 for raw material. teak wood raw material. Based on the wood raw materials, it is necessary to plan to produce each product for each type of wood, but due to the large number of companies that produce similar products, it can certainly lead to high competition, with this competition it will certainly affect profits, the company must plan to generate maximum profit based on the resources owned by the company in meeting the demand for the resulting production and it is known that the company's income has decreased and profits are not stable. The purpose of this study was to determine the optimal production amount for each product using the simplex method, while the variables studied were mahogany door frames (X1.1), mahogany window frames (X2.1), mahogany door frames (X3.1). ), mahogany wood loster (X4.1), teak wood door frame (X1.2) teak wood window frame (X2.2), teak wood door leaf (X3.2), teak wood loster (X4.2). The results of the study showed that the optimal amount of production in PD. Meubeul Dua Saudara, namely 149 pieces of teak wood window frames (X2.2) and 89 pieces of teak wood doors (X3.2) with a profit of Rp. 19,350,000/mont.